2012
DOI: 10.1002/mc.21972
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length of tumor tissues and survival in patients with early stage non-small cell lung cancer

Abstract: Telomere shortening leads to genomic instability that drives oncogenesis through the activation of telomerase and the generation of other mutations necessary for tumor progression. This study was conducted to determine the impact of telomere shortening on the survival of patients with early stage non-small cell lung cancer (NSCLC). Relative telomere length in tumor tissues was measured by quantitative polymerase chain reaction in 164 patients with surgically resected NSCLC. The association between telomere len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…telomere shortening as an early event in carcinogenesis (34,37). However, our results are consistent with several previous studies in which longer telomeres have been associated with absence of metastases in OSCC (35), a low grade in intracranial tumors (38), higher overall survival in lung cancer patients (36), and a lower risk of death in patients with prostate tumors (39). Moreover, a lack of correlation between telomere length and clinicopathologic characteristics has also been found in breast (40), colorectal (41), and head and neck (42) tumors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…telomere shortening as an early event in carcinogenesis (34,37). However, our results are consistent with several previous studies in which longer telomeres have been associated with absence of metastases in OSCC (35), a low grade in intracranial tumors (38), higher overall survival in lung cancer patients (36), and a lower risk of death in patients with prostate tumors (39). Moreover, a lack of correlation between telomere length and clinicopathologic characteristics has also been found in breast (40), colorectal (41), and head and neck (42) tumors.…”
Section: Discussionsupporting
confidence: 92%
“…Most of those studies have shown that telomeres are shorter in tumors than in normal tissues (33)(34)(35). However, it can be argued that the genomic stability of a tumor is mostly determined by the length of telomeres in the tumor itself, rather than the tumor: normal tissue telomere length ratio (36). Although our results demonstrated no statistically significant correlation with any clinicopathologic features of OSCCs, longer telomeres in tumors could be considered as an early prognostic marker, since they were present in smaller tumors, tumors with lower stages and histological grades, and tumors without metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have shown that telomeres have unequal lengths in tumors compared with normal tissues [37]. Telomeres determine the genomic stability of a tumor primarily by shortening the telomere lengths in the tumor itself [38]. Previous studies showed that hTERT was a target gene of colorectal cancer [39].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, shorter TL may also be associated with increased risk of death after cancer. Recently, several studies on different types of tumors reported a poor survival in patients with cancer with shorter TL measured in non-small cell lung cancer and leukocytes (10,11). Notably, the study of Weischer and colleagues (11) examining 47,102 cancer individuals followed for 20 years observed that shorter leukocyte TL was associated with reduced survival after cancer, but no risk of early death was reported after stratification for cancer types for 131 urinary tract cancers included in the study.…”
Section: Introductionmentioning
confidence: 99%